Kajian Ergonomi di Sentra Persiapan BCCT: Menggugah Minat Baca-Tulis Anak Usia Dini Melalui Penataan Lingkungan Belajar yang Ergonomis - Laily Hidayati (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2018)
Humans influence and are influenced by their environment. That rule is fully accepted in the study of behavioral science or psychology. Thoughts, feelings, behaviors, and tendencies to act can "change" a situation, and can "changed" because of a situation. Ergonomics is the study of the relationship between humans and their environment, in order to improve the quality of these relationships so as to produce positive situations for humans, as well as positive for their environment. This conceptual writing wants to try to apply the study and the results of ergonomics studies into the practice of early childhood learning, by taking a learning approach that is closely related to environmental structuring, namely a center and circle based learning approach, also known as a Beyond Center and Circle Time (BCCT). Which is one of the centers of learning in the BCCT approach is the preparation center. That is the center for early childhood learning environments arranged in such a way that supports the achievement of the purpose of preparing early childhood to master the ability to read, write, and count. This paper wants to integrate the principles of environmental management of the preparation center, with the psychological fact that effective environmental management can really affect human performance, in this case the achievement of early childhood development in read, write, and count preparation. So that it is expected that the efforts of early childhood education institutions to prepare well the tasks of early childhood development can be increased to the optimal level.